Characteristics of peer-led physical activity programs for older adults: a scoping review - Gabriel Soares de Olinda Aprobato; Lorena Jorge Lorenzi; Andressa Crystine da Silva Sobrinho; Luana Karoline Ferreira; Layana Liss Schwenger; Thamires Gabrielly dos Santos Coco; Paulo Henrique Guerra; Grace Angélica de Oliveira Gomes (Brazilian Society of Geriatrics and Gerontology, 2024)
This scoping review investigates peer-led programs as a strategy to promote physical activity (PA) among older adults, addressing a gap in the literature concerning in-depth assessment of the characteristics, components, and effectiveness of such programs. Seven databases were searched for articles published in English, Portuguese, or Spanish on peer-led initiatives aimed at encouraging PA in older adults. A total of 53 studies were included, with a notable increase in publications since 2018, primarily focusing on randomized clinical trials involving participants of both sexes. The findings highlight that peer leaders typically have an average age of 65.2 years, with a minority having prior training in PA, although over half received specific training for leading PA programs. These programs, which predominantly span 1 to 4 months, often involve resistance exercises, walking, and flexibility/stretching/mobility activities, conducted in homes and community spaces. Despite the substantial number of studies utilizing peer-led approaches, a consistent lack of detailed reporting on the specific characteristics of peer leaders was observed, underscoringa need for more comprehensive documentation to enhance the understanding and implementation of these programs for older adults.